Kebutuhan Pengembangan Kompetensi Profesional Melalui Pelatihan Penulisan Jurnal Penelitian Tindakan Kelas - Wahira, Wahira (Universitas Negeri Makassar, 2016)
The general objective of this study was to determine the development needs of profesional competence through training PTK journal writing in primary school teacher. Method used R & D model design development models Borg and Gall were 10 steps. Based on the ten steps tersebutoleh Sukmadinata modified into three steps of research and development, the research phase developed, namely: (1) the preliminary study stage as needs and contens analysis, (2) the development stage as the design, development, and evaluation, (3) stages of testing the effectiveness of product as a semi-sumative evaluation. This research was conducted only at a preliminary stage only and R & D. The data collection technique through, questionnaires and dokumentasi.Subjek research on teachers in KabupatenTakalar which numbered 40 people. The results showed the development requirements of profesional competence through training journal writing PTK elementary school teacher in Takalar category really need or very important. And judging by the results of the assessment of teacher performance in the unfavorable category of profesional competence.